Experience in the validation of a digital marketing methodology to strengthen the hotel sector in the city of Girardot and its area of influence - Sánches, Oscar Javier
This article describes the development of the research project “Validation of a digital transformationmethodology applying marketing enriched with digital content. Case study of the hotel sector, Girardot,Cundinamarca”, which consisted of the bibliographic review of applicable methodologies for the developmentof digital marketing strategies, their application and the validation of results obtained from six hotels.For the selection of the methodology, a bibliographic review was carried out in search of differentmethodological alternatives. According to the information studied, the methodology proposed by Sainz deVicuña is selected, against this information an experiment applied in six hotels was designed, generating adiscussion around the different findings, allowing decisions that contributed to the proposal of a strategy of digital marketing and presenting alternatives to strengthen aspects of the administrative structure ofcompanies. The project was developed during 2020 under confinement situations due to the COVID-19contingency, affecting the hotel sector and generating a problem that became an opportunity by showingthe need to adapt to a changing environment, oriented to digital strategies to strengthening, acquiring andretaining customers. The project ends with the presentation of the results obtained in three meetings, eachin order to maintain contact and present progress. In front of each meeting the businessmen presentedobservations that allowed to validate the decisions taken against the proposed methodology, in the lastmeeting all the products with the suggested changes were socialized.